2013
DOI: 10.1155/2013/458989
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Schizophrenia Adverse Drug Interactions through a Network Approach and Drug Classification

Abstract: Antipsychotic drugs are medications commonly for schizophrenia (SCZ) treatment, which include two groups: typical and atypical. SCZ patients have multiple comorbidities, and the coadministration of drugs is quite common. This may result in adverse drug-drug interactions, which are events that occur when the effect of a drug is altered by the coadministration of another drug. Therefore, it is important to provide a comprehensive view of these interactions for further coadministration improvement. Here, we extra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 25 publications
0
7
0
3
Order By: Relevance
“…The rationale of this inference was based on the assumption that drugs having same targets with SCZ drugs, or drugs whose targets have direct interactions with SCZ drug target, might be potential SCZ drugs. In our previous study, we collected 32 SCZ drugs [ 36 ]. In this study, we updated the drug list by manually checking the drugs' indication field in the DrugBank.…”
Section: Methodsmentioning
confidence: 99%
“…The rationale of this inference was based on the assumption that drugs having same targets with SCZ drugs, or drugs whose targets have direct interactions with SCZ drug target, might be potential SCZ drugs. In our previous study, we collected 32 SCZ drugs [ 36 ]. In this study, we updated the drug list by manually checking the drugs' indication field in the DrugBank.…”
Section: Methodsmentioning
confidence: 99%
“…These existing works suggest that various types of data are potentially useful in predicting drug properties. Network-based approaches have been proposed to discover novel drug-target interactions [5]- [7], drug-drug interactions [8], [9], [11], and drug adverse reactions [10]. In these approaches, networks containing drugs and drug property entities are created, and the network features, such as common neighbors or the number of paths, are used to predict drug properties.…”
Section: Related Workmentioning
confidence: 99%
“…We utilize the structure of the drug graph to quantify the edge likelihood. As it has been shown that the structure of networks that represent relationships among drugs and drug properties can effectively help to discover novel drug properties [5]- [11], we quantify edge likelihood based on the number of paths between two nodes. However, in contrast to previous works in which the networks contain limited types of nodes, our drug graph contains various node types, and our approach takes into account the types of nodes along the paths in order to leverage the semantics in the heterogeneous drug graph.…”
Section: Introductionmentioning
confidence: 99%
“…Other drug-target databases have become available to assist further computational analyses [ 9 , 10 ]. Furthermore, the concept of network medicine has been proposed and various approaches have been developed to assist with drug-drug and drug-target discovery [ 11 14 ]. We recently applied network pharmacology approach to exploring the features of antipsychotic and illicit drugs as well as their targets and found some interesting drug-target interaction features [ 13 15 ].…”
Section: Introductionmentioning
confidence: 99%